The Drosophila Transcription Factors Tinman and Pannier Activate and Collaborate with Myocyte Enhancer Factor-2 to Promote Heart Cell Fate - Lovato, TyAnna L. (PLoS One, 2015)
Expression of the MADS domain transcription factor Myocyte Enhancer Factor 2 (MEF2) is regulated by numerous and overlapping enhancers which tightly control its transcription in the mesoderm. To understand how Mef2 expression is controlled in the heart, we identified a late stage Mef2 cardiac enhancer that is active in all heart cells beginning at stage 14 of embryonic development. This enhancer is regulated by the NK-homeodomain transcription factor Tinman, and the GATA transcription factor Pannier through both direct and indirect interactions with the enhancer. Since Tinman, Pannier and MEF2 are evolutionarily conserved from Drosophila to vertebrates, and since their vertebrate homologs can convert mouse fibroblast cells to cardiomyocytes in different activator cocktails, we tested whether over-expression of these three factors in vivo could ectopically activate known cardiac marker genes. We found that mesodermal over-expression of Tinman and Pannier resulted in approximately 20% of embryos with ectopic Hand and Sulphonylurea receptor (Sur) expression. By adding MEF2 alongside Tinman and Pannier, a dramatic expansion in the expression of Hand and Sur was observed in almost all embryos analyzed. Two additional cardiac markers were also expanded in their expression. Our results demonstrate the ability to initiate ectopic cardiac fate in vivo by the combination of only three members of the conserved Drosophila cardiac transcription network, and provide an opportunity for this genetic model system to be used to dissect the mechanisms of cardiac specification.